2019
DOI: 10.1111/nph.15676
|View full text |Cite
|
Sign up to set email alerts
|

A novel fungal effector from Puccinia graminis suppressing RNA silencing and plant defense responses

Abstract: Summary Fungal plant pathogens, like rust‐causing biotrophic fungi, secrete hundreds of effectors into plant cells to subvert host immunity and promote pathogenicity on their host plants by manipulating specific physiological processes or signal pathways, but the actual function has been demonstrated for very few of these proteins. Here, we show that the PgtSR1 effector proteins, encoded by two allelic genes (PgtSR1‐a and PgtSR1‐b), from the wheat stem rust pathogen Puccinia graminis f. sp. tritici (Pgt), su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 53 publications
(105 reference statements)
1
50
0
1
Order By: Relevance
“…Our study identified 62 Pst Avr candidates through comparative genomics and association analyses. With the identification of more effectors in Puccinia species in recently years [20,25,31,72], functional verification using RNA silencing and transient expression systems should be plausible approaches to identify Pst effectors. Confirmation of the roles of these effector candidates in the future studies is very likely to clone Avr genes in Pst, which should shed light on the mechanisms of interactions between the host and pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified 62 Pst Avr candidates through comparative genomics and association analyses. With the identification of more effectors in Puccinia species in recently years [20,25,31,72], functional verification using RNA silencing and transient expression systems should be plausible approaches to identify Pst effectors. Confirmation of the roles of these effector candidates in the future studies is very likely to clone Avr genes in Pst, which should shed light on the mechanisms of interactions between the host and pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Effectors are essential virulence proteins produced by microbial pathogens to defeat host immunity (Dodds and Rathjen, 2010;Dou and Zhou, 2012). Effectors with RNAi suppression activities have been reported in numerous viruses (Burgyán and Havelda, 2011), several species of Phytophthora (Qiao et al, 2013;Xiong et al, 2014;Zhang et al, 2019), and the fungus Puccinia graminis (Yin et al, 2019). The identification of these viral, Phytophthora, or fungal suppressors of RNA silencing supports plant sRNAs as antimicrobial agents in the corresponding pathosystems.…”
Section: The Prevalence Of Trans-species Rnai In Plantsmentioning
confidence: 99%
“…TAL与植物寄主靶基因相互结合是一种特异性的蛋白 质与DNA结合方式. 在TAL效应子的应用中, 可以利用 分子密码发掘抗病基因和感病基因 [33] , 比如Boch等 [36] . 据预测, 每个疫霉菌种均可编码数百到上 千种效应子, 这些效应子在植物宿主体内具有不同的 细胞功能 [37] .…”
Section: 菌中的Cfem蛋白进行检测发现 22个cfem分泌蛋白unclassified